Electrochemical performance of activated carbon derived from empty fruit bunch via chemical and physical activation method - Hasan Marzukia,; Alya Naili Rozhan,; Hadi Purwanto, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Empty fruit bunch (EFB) is a promising materials to produce activated carbon for electrode materials applications in an energy storage device due to its low cost, high availability and porosity. EFB will require further processing to convert it into activated carbon to enhance its electrochemical performance. In this research, a two-step activation was utilized, in which EFB undergone pyrolysis at 500 °C before being activated via chemical and physical activation methods under various conditions to produce activated carbon. The samples were then characterized using weight loss analysis, Field Emission Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (FESEM-EDX) and Raman Spectroscopy to evaluate their physical characteristics. Cyclic voltammetry (CV), galvanostatic charge discharge (GCD) and electrochemical impedance spectroscopy (EIS) were performed to evaluate their electrochemical performance. The specific capacitance measured from CV analysis shows better performance for samples from physical activation which were in the range of 24 to 140 F/g compared to samples from chemical activation that resulted in only 36 to 90 F/g. These results suggested that physical activation has yielded better electrochemical performance of activated carbon which was influenced by the higher activation temperature in comparison with that of the chemical activation that was performed at lower activation temperature.